INDONESIAN FOOD NEOPHOBIA SCALE AND ITS APPLICATION ON ETHNIC FOOD STUDY - Probo Y. Nugrahedi; Yohanes Kristo Sugiarto Utomo; Inneke Hantoro (Soegijapranata Catholic University, 2024)
Indonesia is rich with traditions and ethnicities, including the ethnic foods. The acceptance of ethnic food to consumers, especially with regards to culinary tourism, should be fully considered. However, food neophobia can be one of the traits that determine consumer acceptance of ethnic food. Measurement of food neophobia has been developed in the form of Food Neophobia Scale (FNS). Nevertheless, the cross-country application of this scale could impact in result bias as different language and cultural perception of each item in the questionnaire could be perceived differently. This study aims to develop a suitable and reliable Indonesian version of FNS and to test it among respondents towards several ethnic foods. Results show that the Indonesian version of FNS is reliable and valid. Application of FNS to measure the degree of neophobia in ethnic foods, namely pempek Palembang, sayur umbut rotan, ayam betutu, and sate ulat sagu, to 100 respondents shows the variety of neophobia levels that could be due to the respondent familiarity to the ethnic foods. We therefore propose the Indonesian FNS to be reliable and valid for its application to assess food neophobia trait in Indonesia.